Temozolomide and oral etoposide in children with recurrent malignant brain tumors - Antonio Ruggiero; Anna Ariano; Silvia Triarico; Michele Antonio Capozza; Alberto Romano; Palma Maurizi; Stefano Mastrangelo; Giorgio Attinà (BioExcel Publishing Ltd, 2020)
Despite advances in the treatment of brain tumors, the prognosis of children with recurrent malignant brain tumors remains poor. Etoposide (VP-16), an inhibitor of nuclear enzyme deoxyribonucleic acid (DNA)-topoisomerase II, has shown activity in brain tumors. Its efficacy appears schedule dependent but, to date, the most effective schedule of administration has not been well defined. Temozolomide (TMZ), like VP-16, penetrates the blood-brain barrier and has activity against malignant brain tumors. This novel alkylating agent is rapidly absorbed and is highly bioavailable after oral administration. The antitumor activity of TMZ has been shown to be schedule dependent. Based on the evidence of different mechanisms of cytotoxicity, TMZ and VP-16 have been utilized in combination in patients with malignant brain tumors. This review evaluates the results derived from the combination use of TMZ and oral VP-16. The reported data suggest potential activity of oral VP-16 and TMZ alone or in combination. Further clinical trials are needed to explore and confirm their promising activity in relapsed brain neoplasms.